Health‐related quality of life 90 days after stroke assessed by the International Consortium for Health Outcome Measurement standard set. (7th September 2020) - Rimmele, D. L.; Lebherz, L.; Frese, M.; Appelbohm, H.; Bartz, H.‐J.; Kriston, L.; Gerloff, C.; Härter, M.; Thomalla, G.
Abstract : Background and purpose: Stroke has detrimental effects in multiple health domains not captured by routine scales. The International Consortium for Health Outcome Measurement has developed a standardized set for self‐reported assessment to overcome this limitation. The aim was to assess this set in acute stroke care. Methods: Consecutive patients with acute ischaemic stroke, transient ischaemic attack or intracerebral hemorrhage were enrolled. Demographics, living situation and cardiovascular risk factors were collected from medical records and interviews. The Patient‐reported Outcomes Measurement Information System 10‐Question Short Form (PROMIS‐10) and the Patient Health Questionnaire‐4 (PHQ‐4) were conducted 90 days after admission. Linear and logistic regression analyses were used to identify predictors of outcome. The study is registered at ClinicalTrials.gov, NCT03795948. Results: In all, 1064 patients were enrolled; mean age was 71.6 years, 51% were female, and median National Institutes of Health Stroke Scale (NIHSS) on admission was 3. Diagnosis was acute ischaemic stroke in 74%, transient ischaemic attack in 20% and intracerebral hemorrhage in 6%. 673 patients were available for outcome evaluation at 90 days; of these 90 (13%) had died. In survivors, t scores of PROMIS‐10 physical and mental health were 40.3 ± 6.17 and 44.3 ± 8.63, compared to 50 ± 10 in healthy populations. 16% reported symptoms indicating depression or anxiety on the PHQ‐4. Higher NIHSS, prior stroke and requiring help pre‐stroke predicted lower values in physical and mental health scores. Higher NIHSS and diabetes were associated with anxiety or depression. Conclusions: Integrated in the routine of acute stroke care, systematic assessment of patient‐reported outcomes reveals impairments in physical and mental health. Main predictors are severity of stroke symptoms and comorbidities such as hypertension and diabetes.